Workplace Interactional Demands and Work-Family Enrichment: An Investigation From the Service Sector - Solat, Saira; Abrar, Muhammad; Shabbir, Rizwan; Bashir, Mohsin; Saleem, Sharjeel; Saqib, Shahnawaz (Frontiers in Psychology, 2020)
Emotional labor has, so far, been found to have negative consequences for service sector employees’ personal well-being. This study strives to look at the positive aspect of emotional labor in the interactive jobs. This research focuses on employees’ psychological needs fulfillment through workplace interactions. The current research is an effort to highlight the importance of workplace interactions through fulfilling the employees’ need for relatedness and personal accomplishment, which triggers positive resources that can be transferred from work domain to home domain and might induce work-family enrichment. Primary data were gathered through self-administered questionnaires. The target population was nurses working in public and private hospitals located in Faisalabad, Lahore, and Multan cities of the province of Punjab, Pakistan. This sector needs the attention of the policymakers if we want to enhance the performance of health sector employees and to improve their work-home enrichment as a healthy worker is a productive worker. Demographic characteristics of respondents have been identified through SPSS while Structural Equation Modeling (SEM) was used as multivariate data analysis tool for statistical analysis. Assessment of measurement and structural model was found satisfactory. The results showed that workplace interactional demands had a significant positive effect on work-family enrichment. Moreover, relatedness and personal accomplishment partially mediated the relationship between workplace interactional demands and work-family enrichment. The findings of the study revealed that workplace interactions are critical in fulfilling the basic psychological needs of individuals and as a result, they find themselves energized and achieve their full potential through the fulfillment of their need for relatedness and accomplishment. This energy is a valuable resource that can enrich their family life.